PERPUTARAN KAS, PERPUTARAN PERSEDIAAN, DAN PERPUTARAN PIUTANG DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL TERHADAP PROFITABILITAS (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2014 - Virginia Elsa Haryono; G. Anggana Lisiantara (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
The purpose of this studies is to examine relation influence cash turnover, inventory turnover, receivable turnover and firm size as a control variable on the profitability of manufacturing companies in the consumer goods industry sector in the Indonesia Stock Exchange for the period of 2014-2017. This studies conducted on 149 sample sector consumer goods manufacturing companies that published annual report in period of 2014-2017 used Rupiah. This studies was quantitative studies by using multiple linear regression. The result of study concluded that that cash turnover, inventory turnover, and receivable turnover were proved did not have influence on profitability (ROA). Keyword: cash turnover, inventory turnover, and receivable turnover